Optimizing GPS L2P Radio Occultation Processing for COSMIC-2 Atmospheric Bending Angle Retrieval - Guo, Sheng; Zhang, Shaocheng; He, Youlin; Wang, Sicheng; Sheng, Zheng; Meng, Xiangguang; Yu, Tao (IEEE transactions on geoscience and remote sensing, 2025)
For the second Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC-2) Global Positioning System radio occultation (GPS RO) neutral atmosphere retrieval, ionosphere error correction on bending angle is performed by combining either L2C or L2P signals with L1 at the University Corporation for Atmospheric Research (UCAR), Boulder, CO, USA. While the L2C is a civil signal, the encrypted L2P signal from high-noise occultations will lead to low-accuracy bending angle profiles. This study distinguishes high-noise COSMIC-2 L2P occultations using the L2P signal-to-noise ratio (SNR) and proposes an alternative ionosphere correction method by fitting and extrapolating the difference between the L1 bending angle and the bending angle derived from the MSIS 00 model above 35 km ( {α }_{\text {L1+M}} ). Statistical validations are performed based on over 110159 L2P occultations from January 2023 to June 2023. The comparison of {α }_{\text {L1+M}} and L1 and L2P bending angle, derived from L2P occultations with SNR below 200 v/v ( {α }_{\text {{L}1}+{\text {ML}}} and {α }_{\text {{L}1+L}{2}{\text {PL}}} ), shows that the percentage passed quality control increased from 40.8% (39.5%) to 73.6% (69.0%) for rising (setting) occultations. The mean standard deviation (SD) of {α }_{\text {L1+M}} is 2.0% (1.9%) on impact heights between 19 and 30 km for rising (setting) occultations, which is obviously smaller than 2.6% (2.5%) for {α }_{\text {L1+L2PL}} profiles. Hence, it can be concluded that the proposed ionosphere correction method can be utilized for retrieving COSMIC-2 L2P occultations, and combined with L2P high SNR occultations, the COSMIC-2 L2P occultations can further enrich the amounts of effective profiles on numerical weather prediction (NWP) and climate research.